Frond Pruning Enhanced The Growth and Yield of Eight-Year-Old Oil Palm (Elaeis guineensis Jacq.) - Marcelino, Junito P.; Diaz, Elvie V. (Annals of Tropical Research, 2016)
Pruning of fronds in oil palms is the subject of interest in oil palm farming that is often based on individual experience and casual observation rather than experimental evidence. Frond pruning in a scientific approach pose useful information in oil palm industry. This study was conducted to find out if frond pruning affects growth and yield of eight-year-old oil palm plantation owned by Kenram Industrial Development Incorporated (KIDI), Isulan, Sultan Kudarat, Philippines from 2011-12. This experiment was laid out in Randomized Complete Block Design with four treatments replicated three times. Standard guide on fertilization, cultural management practices, control of insect pest and diseases, and harvesting of bunches for oil palms were followed. Fronds were pruned according to the number of fronds retained per treatment except for those without pruning. Agronomic and yield parameters were gathered, statistically analyzed while variances among treatments were subjected to DMRT. Frond pruning in oil palm plants significantly affected fruit bunch production specifically on the number and weight of harvested bunches. However, no significant effect was observed on its agronomic characteristics. The retention of 32 – 40 fronds per tree produced more and heavier bunch compared to plants with 24 fronds and plants without frond pruning. Optimum fronds are required to obtained better yield. Palms without frond pruning and those with excessive pruning below 32 fronds produced lesser and lighter bunches.